Multi-stage thermal-economical optimization of compact heat exchangers: A new evolutionary-based design approach for real-world problems - Yousefi M.; Darus A.N.; Yousefi M.; Hooshyar D. (Elsevier Ltd, 2023)
Algorithms; Constraint theory; Design; Entropy; Fins (heat exchange); Genetic algorithms; Heat exchangers; Particle swarm optimization (PSO); Thermodynamics; Compact heat exchanger; Engineering applications; Entropy generation minimization; Evolutionary algorithms (EAs); Inequality constraint; Multi stage; Plate-fin heat exchanger; Variable operating condition; Evolutionary algorithms